A study on water quality at Sungai Pandan - Mohamad Hafizuddin, Mohd Yusri (2019)
The river has many important uses, it is very important for its quality to be monitored and reviewed continuously. Therefore, the objective of this study is to determine the Water Quality Index (WQI) of Sungai Pandan based on the six parameters in the scope of the WQI Water Quality Index, and to see the effectiveness of the river water treatment method using two types of coagulants Aluminium Sulphate and Iron Sulphate or better known as Ferric Sulphate. Based on the results of the study, the WQI value for Sungai Pandan is between 88.96 (downstream) up to 97.62 (upstream). This value was obtained after taking into account the six sub-indexes of the WQI parameters: Dilute Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Suspended Solids (TSS), Nitrogen Ammonia (AN) and pH. For the determination of the Pandan River classification, the WQI value has been shown to indicate that Pandan River is under Class I until Class II. For comparison of both coagulant, Aluminium Sulphate was better for removal of turbidity and suspended solids. The percentage of turbidity removal for Aluminium Sulphate at each station is between 38.76% and 60.98%, while for Ferric Sulphate is only between 21.14% and 36.41%. In general for the removal of turbidity and suspended solids, Aluminium Sulphate is better than Ferric Sulphate. For the removal of suspended solids, for each station the percentage of removal by Aluminium Sulphate is between 30.77% and 48.48% and it is higher than Ferric Sulphate which is only between 12.5% and 33.33%. It is clear that Aluminium Sulphate is better to remove suspended solids than Ferric Sulphate. For the removal of heavy metals, Ferric Sulphate is much superior to Aluminium Sulphate. For Copper, Aluminium Sulphate has removed metal percent between 5.88% and up to 25% at each station while Ferric Sulphate ranges from 17.65% to 33.33%. For Chromium metal, Aluminium Sulphate eliminates 10.34% up to 29.63% while Ferric Sulphate can get rid of 11.11% up to 37.63%. For Zinc metal, 3.57% to 56.25% for Aluminium Sulphate while 6.06% to 59.38% can be removed by Ferric Sulphate. Clearly, the removal of heavy metals Ferric Sulphate is better than Aluminium Sulphate.